Pendampingan Kader dalam Pengolahan dan Pemberian Makanan Pendamping ASI berbasis Kearifan Lokal - Asri Aprilia Rohman; Tita Rohita; Nina Rosdiana; Arifah Septiane Mukti (Yayasan Inspirasi El Burhani, 2022)
Introduction: Childhood (up to two years old) is a golden period of growth and development that determines the quality of future health. Several factors play an important role for physical growth and development, including nutritional and non-nutritional factors. Nutritional problems, including stunting (dwarf), during childhood will hinder the process of growth and development and increase the risk of degenerative diseases or chronic noncommunicable diseases (NCDs) in later stages of life. Objective: This service activity aims to increase the knowledge of cadres about MP ASI and improve the ability of cadres in processing MP ASI Method: The methods used in this community service are lectures, discussions, and exercises to process MP ASI directly. Result: Based on the results of the training, it was found that there was an increase in the knowledge of cadres with an average increase in post test results of 17.2 with the highest score on the post test being 100. Conclusion: The implementation of this service activity has been carried out smoothly and according to plan, followed by 18 cadres from village representatives who are in the working area of the Bregbeg Health Center who are very enthusiastic and eager to participate in this activity to completion . There is a significant difference in the knowledge of cadres in the processing and provision of complementary feeding assistance compared to before participating in the mentoring (test score from 65.7 to 82.9).